THE USE OF ENGLISH COMICS “AVENGERS” FOR ENRICHING STUDENT’S VOCABULAR MASTERY: A CASE OF THE EIGHTH GRADE STUDENTS OF SMPN 20 SEMARANG - Susanti Susanti (Universitas PGRI Semarang, 2014)
In teaching learning process, one of the important components of the English language is vocabulary since it is the most important thing in conducting communication. But the students often get problems in expressing their ideas as they are lack of vocabularies. To enrich their vocabularies, a treatment is given to them. The treatment is teaching vocabulary by using English comic Avengers for the experimental group. The problems of this study are: How is the result of using English comics as a medium in teaching English vocabulary?. Is comic effective as a medium in teaching English vocabulary?. From pre-test (44.0625) to post-test (62.5) for control group and pre-test (44.69) to post-test (72.81) for experimental group. It means that the use English comic is effective for enriching vocabulary mastery.The t-test result showed that t-test was 3.47 and the t-table for 5% was 1.67. It means that t-test was higher than t-table (3.47>1.67).